The Role of The State in Protecting Children After Divorce: A Legal Analysis of Family Law in Indonesia - Nurhaida, Heni Satar (Unram Law Review, 2025)
This study explores post-divorce child protection in Indonesia, focusing on the research methodology and relevant discussion results. Qualitative research methods were employed to investigate the experiences and views of parents and experts regarding the implementation of child protection laws after divorce. The results indicate that, although there are regulations governing children's rights, their implementation is often hampered by social, economic, and cultural factors. The findings also suggest that uncertainty in court decisions regarding custody and support negatively impacts children's welfare. This discussion emphasizes the need for more effective law enforcement mechanisms and psychological support for children and parents after divorce. Recommendations from this study include strengthening the capacity of relevant institutions to implement the law and providing assistance programs for families. With an integrated approach, it is hoped that child protection can be carried out comprehensively and sustainably, allowing affected children to grow up in a healthy and safe environment.